Unfolding the debate on safety culture: Exploring a multi-thematic operational process sensitive to divergence. - Abraçado, Mateus Pereira; de Oliveira, Eliel Prueza; Lima, Francisco de Paula Antunes; Rocha, Raoni; Pereira, Vitor Fernando S G; Duarte, Francisco José de Castro Moura (Work, 2026)
Background: Contemporary safety culture studies emphasize the interplay between formal and informal organizational practices, yet often overlook internal divergences and power dynamics, and competing interests in diagnosing maturity. Addressing this gap, this study integrates the analysis of controversies and divergences as central to diagnosing and fostering safety culture maturity, thereby acknowledging the inseparable link between culture and power. Objective: This research aims to demonstrate how a divergence-sensitive, multi-thematic approach, grounded in mixed methods, can refine safety culture diagnostics and stimulate organizational learning. Methods: A mixed-methods intervention was conducted within an energy production company. The quantitative phase involved administering an 80-item customized questionnaire to homogeneous groups, assessing safety culture maturity levels based on five key themes: blame, rule relevance, safety prioritization, safety bureaucracy, and operational experience feedback. The qualitative phase comprised discussion groups that explored divergences identified in the quantitative results, allowing for adjustments to maturity level classifications. Results: The analysis of 43 cases revealed that recognizing divergences facilitated more precise maturity assessments. In several instances, maturity levels were adjusted based on qualitative insights, highlighting the limitations of purely quantitative evaluations. The study also provided a conceptual framework for interpreting maturity levels across the five themes, grounded in both literature and empirical findings. Conclusions: The divergence-sensitive approach proved effective in enhancing safety culture diagnostics and promoting internal debate. Recognizing divergences not as dysfunctions but as opportunities for organizational learning fosters a mature safety culture capable of managing uncertainty through provisional consensus and collaborative experimentation.